Lack of Reproductive Isolation in Helicoverpa gelotopoeon (Lepidoptera: Noctuidae) Populations from Different Host Plant Species in Argentina - Herrero, María Inés (2019)
Helicoverpa gelotopoeon (Dyar) (Lepidoptera: Noctuidae) is a polyphagous pest that belongs to the Heliothinae complex, and has been described as feeding on numerous crops. Larvae damage mainly pods and seeds of soybean and other legumes. Adaptation to different host plants might reduce gene flow between phytophagous insect populations, which could lead to reproductive isolation. Therefore, studies on gene flow among host-associated populations are necessary to design management strategies. The objective of this study was to evaluate reproductive compatibility between 2 populations of H. gelotopoeon coming from different host plants. We collected H. gelotopoeon larvae in alfalfa and soybean crops, and studied biological and reproductive parameters, and mating compatibility. Helicoverpa gelotopoeon populations from soybean and alfalfa reared on artificial diet showed similar biological and reproductive characteristics. Intra- and inter-population crosses revealed that there are no signs of host-associated isolation, allowing gene exchange between these populations, which can be explained by the high mobility and generalist behavior of this species. This information will be useful to establish control measures for this pest.